Sensory traits of capon meat in three chicken genotypes - Špela MALOVRH; Katarina HRIBERŠEK; Dušan TERČIČ; Marko VOLK; Božidar ŽLENDER; Tomaž POLAK; Antonija HOLCMAN (Acta Agriculturae Slovenica, 2009)
Capons of three genotypes (Barred Prelux, Sulmtaler, Styrian hen) were fattened outdoors and slaughtered at two ages (163 and 198 days). Cockerels were caponised at age 47 days and at age 84 days were moved to grower houses with free access to pasture. Animals had ad libitum access to food and water. Ten carcasses of each genotype and age were sampled at slaughter for sensory analysis. The four trained panellist assessed three traits of raw carcasses on scale 1–5 and 19 traits on roasted carcasses on scale 1–7. Shear force was measured on cooled meat slices by apparatus Texture Analyser, TA.XT plus, Volodkevich contact cell. Statistical analysis was performed by MIXED procedure in SAS/STAT. Age at slaughter affected nine, genotype five and interaction between age and genotype three sensory traits. Shear force differed among genotypes and it got worse at older age. Any of three genotypes was not superior in most of sensory traits. Thus, decision which genotype to fatten and how long depends on preferences and importance of certain sensory traits by consumers.